Private investments in modern foodgrain storage in Bangladesh: An economic feasibility analysis and potential role for the public sector - Chowdhury, Reajul Alam; Alam, Md. Monjurul; Ali, Md. Rostom; Awal, Md. Abdul; Hossain, Shahadat; Kalita, Prasanta Kumar; Saha, Chayan Kumer; Winter-Nelson, Alex (International Food Policy Research Institute, 2021)
Unprecedented growth in rice production in Bangladesh over the last four decades has outpaced the capacity of post-harvest operations, resulting in substantial grain losses. While production technology has changed dramatically over time, there has been relatively little private investment in transforming storage capacity in the country. This paper explores the lack of widespread private investment in improved grain storage and examines the potential for public support to stimulate greater private sector investment in modern storage. We calculate the returns to investment in bulk grain silos and hermetic cocoons that could upgrade warehouse storage, and calculate the grain loss that conversion to those technologies would prevent. We then assess the public support that would be required to trigger private investment in modern storage systems.